The influence of familiarity and personal innovativeness on the acceptance of fintech lending services: A perspective from Indonesian borrowers - Wirani, Yekti; Randi, Randi; Romadhon, Muh Syaiful; Suhendi, Suhendi (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2022)
Financial Technology (FinTech) Lending in Indonesia is an innovative solution for financial services in Indonesia because it has convenience and benefits for Indonesians who need loans, fund management, and other financial transaction activities. FinTech Lending is growing fast because it offers reasonable interest rates and access to conventional financial institutions. The growth of FinTech Lending is expected to support financial inclusion planned by the Indonesian government. In 2020, 126 FinTech Lending Companies were operating illegally by exploiting communities experiencing economic difficulties. This study aims to determine the factors that influence the adoption of FinTech services in Indonesia, considering obstacles and occasions. Factors related to obstacles are Trust and Security in Online Lending platforms, while factors related to occasions are Personal Innovativeness, Interest Rate, and Familiarity. This study used a sampling technique, namely purposive sampling, and involved 85 respondents from Indonesian Borrowers with the age majority between 20 to 25 years old. Processes data obtained from survey results using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results are that Familiarity and Personal Innovativeness affect the acceptance of FinTech Lending companies in Indonesia. In addition, it produces guidance for the improvement of FinTech Lending Companies in Indonesia, which be used to develop and support financial inclusion in Indonesia.